Formulasi Sediaan Body Scrub Ekstrak Etanol Daun Salam (Syzygium Polyanthum (Wight.) Walp) dan Serbuk Beras Putih (Oryza sativa L.) Sebagai Pelembab Kulit - Monica Suryani; Julia Susanti; Dumartina Hutauruk (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Body scrub is a pharmaceutical preparation in the form of a beauty product that functions to smooth the skin of the body and remove damaged skin cells with the help of scrubs. Bay leaf (Syzygium polyanthum (Wight.)Walp) and white rice powder (Oryza sativa L.) are plants that are widely used to maintain health, as a traditional medicine and also as an antioxidant. The research method carried out is experimental. The purpose of this study was to formulate ethanol extracts of bay leaf (Syzygium polyanthum (Wight.)Walp) and white rice powder (Oryza sativa L.) in the form of Body Scrub preparations with concentrations 2, 4, and 6 that can be used as a skin moisturizer. The extract sample uses ethanol solvent, which will be formulated into the form of a Body Scrub preparation, then an examination of the physical quality test of the preparation, irritation test, hedonic test, moisturiser effectiveness test using a skin moisture analyzer is carried out. The results of this study show that the ethanol extract of bay leaf (Syzygium polyanthum) and white rice powder (Oryza sativa L.) can be formulated as a Body Scrub preparation that has met the physical quality requirements of the preparation which has a semi-solid shape, a more concentrated preparation color and a distinctive aroma of bay leaf extract. The preparation shows a homogeneous composition, M/A cream type, spread power range 5.7-6.2 cm, viscosity range 3,800- 4000 cPs, pH 6.4-6.7, non-irritating to the skin and stable in storage for 4 weeks of storage, hedonic value that is very preferred by researchers on the Body scrub F3 preparation. The effectiveness test showed an increase in humidity of 31.59%, which was the best in the preparation of F3 concentration. It can be concluded that the ethanol extract of bay leaf (Syzygium polyanthum (Wight.)Walp) and white rice powder (Oryza sativa L.) can be formulated in Body Scrub preparations that have met the physical quality requirements of the preparation as a skin moisturizer at a concentration of 6%.